Women against violence against women - Aguilar, Mila D.; Selvido, Ma. Ernie ([Quezon City] The Institute, 1992)
Features the commentaries of three social welfare experts and one victim on the topic of crimes in violation of women.
In English and Pilipino.
Keywords: Women -- Crimes against; Sociology; Social work